2012
DOI: 10.1073/pnas.1114772109
|View full text |Cite
|
Sign up to set email alerts
|

Critical perspectives on historical collapse

Abstract: Historical collapse of ancient states or civilizations has raised new awareness about its possible relevance to current issues of sustainability, in the context of global change. This Special Feature examines 12 case studies of societies under stress, of which seven suffered severe transformation. Outcomes were complex and unpredictable. Five others overcame breakdown through environmental, political, or socio-cultural resilience, which deserves as much attention as the identification of stressors. Response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
129
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(129 citation statements)
references
References 39 publications
0
129
0
Order By: Relevance
“…There have been many definitions and much discussion of past 'collapses' [1,3,[28][29][30][31], but a future global collapse does not require a careful definition. It could be triggered by anything from a 'small' nuclear war, whose ecological effects could quickly end civilization [32], to a more gradual breakdown because famines, epidemics and resource shortages cause a disintegration of central control within nations, in concert with disruptions of trade and conflicts over increasingly scarce necessities.…”
Section: Do Current Trends Portend a Collapse?mentioning
confidence: 99%
“…There have been many definitions and much discussion of past 'collapses' [1,3,[28][29][30][31], but a future global collapse does not require a careful definition. It could be triggered by anything from a 'small' nuclear war, whose ecological effects could quickly end civilization [32], to a more gradual breakdown because famines, epidemics and resource shortages cause a disintegration of central control within nations, in concert with disruptions of trade and conflicts over increasingly scarce necessities.…”
Section: Do Current Trends Portend a Collapse?mentioning
confidence: 99%
“…Many other scholars strongly object to these dogmatic statements as a simplistic, monocausal approach to the study of climatic impacts on the fortunes of historical societies (Rosen, 2007;Butzer and Endfield, 2012). A typical example is the Classic Maya collapse.…”
Section: Introductionmentioning
confidence: 99%
“…The process is not always successful. In a recent study of societies under severe stress, Butzer and Endfield (2) found that less than half were able to avoid breakdown. Adaptive social learning is not an easy challenge to meet.…”
mentioning
confidence: 99%